E-040 Initial Multi-Centre Experience with the Penumbra PC 400 Detachable Coil. (14th July 2013) - Patel, A; Moyle, H; Chaudry, I; Frei, D; Bellon, R; Huddle, D; Baxter, B; Quarfordt, S; Turner, R; Turk, A
Abstract : Introduction/Purpose: Aneurysm coil technology has changed considerably since the introduction of the GDC coil. We evaluated our initial clinical experience with a novel 0.020 Penumbra PC 400 coil to determine device safety and acute performance. Materials and Methods: Between 2/2011 and 9/2012, 133 aneurysms were coiled with Penumbra PC 400 coils; 84 elective and 49 ruptured, at four high volume centres. Results: Average aneurysm size was 8 mm with 28% PCOM, 43% other ICA locations, 21% ACOM and the remaining Basilar, MCA and Vertebral. 15% of the cases were treated with balloon assisted coiling, 18% were stent assisted coiling, and 4% utilised both balloons and stents. Packing density could be accurately calculated in 97 aneurysms. Average packing density was 38.7%. 32% of the cases achieved an initial Raymond Scale of 1, 24% achieved a Raymond scale of 2, and 43% were Raymond Scale of 3. Almost half (66) of the patients have angiographic follow up at the time of this abstract. Based on the same/better/worse scale, vast majority of aneurysms showed stable or improved angiographic outcomes at 6 months and one year. Thirty-six had improved, 24 remained unchanged and 6 worsened, 0 patients required re-treatment. We experienced a 5% rate of peri-procedural adverse events. 3 (2%) were thromboembolic, all 3 patients were SAH cases, of which 2 had no clinical sequelae. 4 (3%) were aneurysm perforations, 3 with no clinical sequelae, and one SAH H/H grade 4 patient died, resulting in an overall morbidity and mortality of 2 (1.5%). We continue to use the coils and accrue follow up and will update results at the time of the meeting. Conclusion: The new Penumbra PC 400 coils are unique 0.020 coils that show very high average packing density and long term occlusion rates with a safe profile. Disclosures: A. Patel: 3; C; Penumbra, Inc. H. Moyle: None. I. Chaudry: 3; C; Penumbra, Inc. D. Frei: 3; C; Penumbra, Inc. R. Bellon: None. D. Huddle: None. B. Baxter: 3; C; Penumbra, Inc. S. Quarfordt: None. R. Turner: None. A. Turk: 3; C; Penumbra, Inc.